“Gamificación como estrategia de aprendizaje de la neuroeducación para la asignatura educación cultural y artística” - Álvarez Sangoquiza, Ángel Mesías (2020)
This investigation is based on the problem identified in the “Agustín Albán” school, which lacks a gamification strategy for the teaching of Cultural and Artistic Education applied to ICT in children in the seventh grade of E.G.B .; the general objective is to elaborate a strategy for teaching learning of the referred subject based on gamification as an element of Neuro-education; methodologically it is supported on mixed, descriptive, basic and action research; the methods that were part of the process are: the modeling method, the pedagogical test and the survey, together with their respective instruments; descriptive statistics were used to represent relevant aspects of the research through tables and graphs that offer a global and synthesized view of the study problem; among the main results obtained are determined: in chapter I we define the fundamental theoretical foundations and gamification strategies as part of neuroeducation; chapter II allowed the current diagnosis of the teaching-learning process to be carried out, which reveals a state of insufficiency that demands alternatives to solve the problem; in chapter III a gamified prototype based on the principles of neuroeducation was designed and validated; in conclusion, the strategy for learning the subject based on gamification proves to be highly viable for solving the learning problem.